BODIPY-based conjugated porous polymers for highly efficient volatile iodine capture. Issue 14 (21st March 2017) - Zhu, Yunlong; Ji, Ya-Jian; Wang, De-Gao; Zhang, Yi; Tang, Hui; Jia, Xin-Ru; Song, Min; Yu, Guipeng; Kuang, Gui-Chao
Abstract : Two novel BODIPY-based conjugated porous polymers were prepared for the adsorption of volatile iodine. Abstract : Capturing volatile radionuclide iodine from nuclear and medical waste streams is an important environmental issue. In this work, we found that the 2, 6-position hydrogen atoms of a BODIPY core undergo fast iodination with volatile iodine at room temperature. Inspired by our observation, two novel BODIPY-based conjugated porous polymers (CPPs)BDP-CPP-1 andBDP-CPP-2, and the reference compoundNBDP-CPP, were prepared, which were designed and then synthesized via the Sonogashira cross-coupling reaction of 1, 3, 5-triethynyl-benzene (TEB) and dibromo-substituted derivatives. With the coexistence of the BODIPY units and plenty of triple bonds and phenyl rings that could adsorb iodine with high capacity and affinity, compoundsBDP-CPP-1 andBDP-CPP-2 exhibited satisfactory iodine adsorption capacities of 2830 mg g −1 and 2230 mg g −1, respectively. Moreover, BDP-CPP-1 was shown to adsorb volatile iodine through a chemical mechanism involving the 2, 6-position hydrogen atoms of the BODIPY core. Surprisingly, the active sites on the BODIPY units for a chemical iodination reaction were mostly eliminated as a result of the crosslinking of BODIPY units during the Sonogashira coupling reaction. The preliminary results demonstrated that the iodine uptake abilities, which are in the order ofBDP-CPP-1 >BDP-CPP-2 >NBDP-CPP, are not only dependent on the surface area, but also on the BODIPY units. The BDP-CPPs show high thermal stability with a decomposition temperature of about 300 °C. In addition, the BDP-CPPs demonstrated remarkable recyclability. Due to the highly π-conjugated porous structure along with the high affinity for iodine molecules and iodination sites, some BODIPY-based CPPs may provide a feasible pathway to adsorb other volatile compounds.